Commercial distress. The speech of D. Urquhart on Mr James Wilson's amendment to the motion of the chancellor of the Exchequer, for the "Appointment of a select committee to inquire into the causes of the recent commercial distress [...] in the House of Commons [...], December 2nd, 1847" (Woodfall], 1847)
Extracted from Hansard's Parliamentary Debates.